From Technical Solutions to Implementation: A Bibliometric Review of Behavioral Barriers in Urban Climate Adaptation - Siti Rahmah Omar; Nur Hidayah Abd Rahman; Nur Emma Mustaffa; Muhammad Farid Azizul (Global Academic Excellence (M) Sdn Bhd, 2026)
Tier 3- Indexed by MyCite